(untitled) (Pesquisa Odontológica Brasileira, 2003)
This research aimed at assessing the relation between the horizontal condylar angle (HCA) and the internal derangement (ID) of the temporomandibular joint (TMJ), as a result of interference by the TMJ disk, in individuals undergoing magnetic resonance (MR) scans. The sample included a total of 144 TMJs (sagittal and coronal views) of 72 subjects, 15 of whom were male and 57 female, with ages ranging from 15 to 70. The scans were made in a Signa system (GE) model at a magnetic field magnitude of 1.5 T. Sixty-eight TMJs were found to be normal, while 46 showed anterior displacement with reduction. Of these, 41 had some kind of adaptive change in the condyle, while 5 showed degenerative changes. Anterior displacement without reduction was found in 29 joints, 12 of which showed adaptative changes in the condyle, while 17 showed degenerative changes. Only one posterior displacement of the articular disk was recorded. For the TMJs in which disk displacement was found, such values achieved 24.69º on the right side, and 22.94º on the left side. Hence, it was possible for us to conclude that the HCA tends to increase in those TMJs where ID is present. For contralateral TMJs, a strong association was observed between HCA values (57.8%), state of normality (69.7%), and ID (66.7%). To corroborate such findings, a correlation between contralateral HCA values (63.31%) and the diagnosis for contralateral TMJs (68.05%) was determined. Thus, we could infer that there is a tendency between contralateral TMJs to share characteristics and conditions.